2022
DOI: 10.3390/ijms23020620
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue-Derived Extracellular Vesicle Mediated Therapy in the Neonatal Ischemic Brain

Abstract: Hypoxic-Ischemic Encephalopathy (HIE) in the brain is the leading cause of morbidity and mortality in neonates and can lead to irreparable tissue damage and cognition. Thus, investigating key mediators of the HI response to identify points of therapeutic intervention has significant clinical potential. Brain repair after HI requires highly coordinated injury responses mediated by cell-derived extracellular vesicles (EVs). Studies show that stem cell-derived EVs attenuate the injury response in ischemic models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…43 The conversion of ALA C18:3 ω-3 to EPA C20:5 ω-3 and DHA C22:6 ω-3 is a crucial metabolic pathway, with DHA playing a vital role as a nutritional component in reducing adverse impacts on neurological development. [44][45][46] Furthermore, OA C18:1 ω-9, a neuroactive molecule, has been utilized in neuropathic pain treatment after neurotrauma, 47 while EA C22:1 ω-9 supplementation has been demonstrated to enhance memory in rats with cognitive impairment. 48 EA C22:1 ω-9 and OA C18:1 ω-9 chains can be elongated and converted into NA C24:1 ω-9 in the brain, as supported by previous research.…”
Section: Papermentioning
confidence: 99%
“…43 The conversion of ALA C18:3 ω-3 to EPA C20:5 ω-3 and DHA C22:6 ω-3 is a crucial metabolic pathway, with DHA playing a vital role as a nutritional component in reducing adverse impacts on neurological development. [44][45][46] Furthermore, OA C18:1 ω-9, a neuroactive molecule, has been utilized in neuropathic pain treatment after neurotrauma, 47 while EA C22:1 ω-9 supplementation has been demonstrated to enhance memory in rats with cognitive impairment. 48 EA C22:1 ω-9 and OA C18:1 ω-9 chains can be elongated and converted into NA C24:1 ω-9 in the brain, as supported by previous research.…”
Section: Papermentioning
confidence: 99%
“…Hypoxic encephalopathy triggers a kind of CNS dysfunction with high mortality and morbidity in neonates and even life‐lasting paralysis 131 . Brain‐derived extracellular vesicles (BEVs) ameliorate the neurotoxicity in oxygen–glucose deprivation (OGD) brain slices based on a dose‐time dependent procedure 132 . Human amniotic fluid‐derived exosomes significantly augment the expression level of hypoxia‐inducible factor 1 α (HIF‐1α) and vascular endothelial growth factor (VEGF) that coincide with a decrease in the escape latency time and increase in the target quadrant occupancy of MWM test 133 …”
Section: Exosome Therapy Enhances Neurorestoration Concurring With Co...mentioning
confidence: 99%
“…Over the past decade, advanced protocols for isolating sEVs from the extracellular space of postmortem brain tissue were developed to understand region‐specific changes associated with pathology (Banigan et al., 2013 , Cohn et al., 2021 , Gallart‐Palau et al., 2016 , Huang et al., 2020 , Hurwitz et al., 2018 , Muraoka et al., 2020 , Nguyen et al., 2022 , Perez‐Gonzalez et al., 2012 , Pérez‐González et al., 2017 , Vella et al., 2017 ). Implementation of these methods demonstrated that levels of sEVs are differentially modulated by various AD risk factors (e.g., APOE4, Down syndrome, APP) as a function of age and disease severity (Gauthier et al., 2017 , Hartley et al., 2015 , Mathews & Levy, 2019 , Peng et al., 2019 , Perez‐Gonzalez et al., 2012 , Wisniewski et al., 1985 ).…”
Section: Introductionmentioning
confidence: 99%